Effectiveness of Long-Acting Reversible Contraception - Winner, Brooke; Peipert, Jeffrey F; Zhao, Qiuhong; Buckel, Christina; Madden, Tessa; Allsworth, Jenifer E; Secura, Gina M (The New England journal of medicine, 2012)
This study involved women at high risk for unintended pregnancy who received free contraception. Long-acting reversible contraception was associated with a significantly lower risk of pregnancy than contraceptive pills, patch, or ring and was highly effective regardless of age. Unintended pregnancy is a major problem in the United States. Approximately 3 million pregnancies per year — 50% of all pregnancies — are unintended, and this rate is significantly higher than that in other developed countries. 1 Unintended pregnancy in the United States results in 1.2 million abortions per year, 2 has negative effects on women's health and education and the health of newborns, and imposes a considerable personal burden as well as a financial burden on families and society. 3 Approximately half of unintended pregnancies result from contraceptive failure, usually owing to incorrect or inconsistent use of contraception, and the remainder are . . .